2022
DOI: 10.3390/nu14235086
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dietary Interventions on Brain Aging and Neurological Diseases

Abstract: Dietary interventions can ameliorate age-related neurological decline. Decades of research of in vitro studies, animal models, and clinical trials support their ability and efficacy to improve behavioral outcomes by inducing biochemical and physiological changes that lead to a more resilient brain. Dietary interventions including calorie restriction, alternate day fasting, time restricted feeding, and fasting mimicking diets not only improve normal brain aging but also slow down, or even reverse, the progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 142 publications
0
8
0
3
Order By: Relevance
“…4.1 Nutritional strategies: Fasting, phytochemicals, phytomelatonin, and fermented food 4.1.1 Fasting Fasting is an effective way to recover mitochondrial efficiency, and multiple human studies have shown its ability to restore metabolic pathways in people suffering from chronic pathologies. Fasting regimens are promising primary and secondary prevention strategies in patients suffering from metabolic and cardiovascular diseases (Oliveira et al, 2022;Papakonstantinou et al, 2022;Vasim et al, 2022;Zang et al, 2022), pain, inflammation and immune conditions (Feng et al, 2022;Fitzgerald et al, 2022;Parveen and Alhazmi, 2022), cancer (Lv et al, 2014;Marinac et al, 2016;Taucher et al, 2022;Tiwari et al, 2022), and neurological diseases characterized by altered mood, sleep, pain, and cognition (Phillips, 2019;Brocchi et al, 2022;Caron et al, 2022;Feng et al, 2022;Lobo et al, 2022;Xu et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…4.1 Nutritional strategies: Fasting, phytochemicals, phytomelatonin, and fermented food 4.1.1 Fasting Fasting is an effective way to recover mitochondrial efficiency, and multiple human studies have shown its ability to restore metabolic pathways in people suffering from chronic pathologies. Fasting regimens are promising primary and secondary prevention strategies in patients suffering from metabolic and cardiovascular diseases (Oliveira et al, 2022;Papakonstantinou et al, 2022;Vasim et al, 2022;Zang et al, 2022), pain, inflammation and immune conditions (Feng et al, 2022;Fitzgerald et al, 2022;Parveen and Alhazmi, 2022), cancer (Lv et al, 2014;Marinac et al, 2016;Taucher et al, 2022;Tiwari et al, 2022), and neurological diseases characterized by altered mood, sleep, pain, and cognition (Phillips, 2019;Brocchi et al, 2022;Caron et al, 2022;Feng et al, 2022;Lobo et al, 2022;Xu et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…КД может успешно применяться для компенсации течения группы тяжелых неврологических заболеваний [9,10] и рекомендована детям в качестве альтернативного способа лечения любой формы эпилепсии при неэффективности традиционно применяемых противоэпилептических препаратов (уровень убедительности рекомендаций А, уровень достоверности доказательств -1) [11].…”
Section: кетогенная диета как альтернативный метод лечения эпилепсииunclassified
“…По определению, традиционная КД -низкоуглеводная диета с высоким содержанием жиров и умеренным содержанием белков, направленная на замену глюкозы кетоновыми телами (КТ) [7][8][9][10]12]. Так называемая модель VLCKD -КД с очень низким содержанием углеводов.…”
Section: кетогенная диета как альтернативный метод лечения эпилепсииunclassified
“…In Alzheimer's disease (AD), changes to the diet have been recommended (Bourre 2006;Power et al 2019;Mao et al 2021;Lobo et al 2022), including MCS (Strupp et al 2016;Velazquez et al 2020;Dave et al 2023;Judd et al 2023a;. One reason for the recommendation is that serum levels of choline are low in individuals with AD (Dave et al 2023;Judd et al 2023b).…”
Section: Introductionmentioning
confidence: 99%
“…In Alzheimer's disease (AD), changes to the diet have been recommended (Bourre, 2006;Power et al, 2019;Mao et al, 2021;Lobo et al, 2022), including MCS (Strupp et al, 2016;Velazquez et al, 2020). The recommendation to use MCS is based primarily on data from the Ts65Dn mouse model of Down syndrome (DS) and AD, where MCS led to improved memory and attention in Ts65Dn offspring (Strupp et al, 2016;Powers et al, 2017;Powers et al, 2021).…”
Section: Introductionmentioning
confidence: 99%